Factors Influencing the Efficacy of Chinese Medicinals - Qichao Liang; Yun Jiang; Liguo Liang; Hualong Liang (Chinese Medicine and Natural Products)
This paper thoroughly explores the multifaceted factors influencing the efficacy of Chinese medicinals and categorizes them into three main groups: medicinal related factors, patient related factors, and practitioner related factors. Regarding medicinal related factors, the place of origin, growing environment, harvesting time, storage conditions, quality control, dosage form selection, compatibility of medicinals, precise dosing, decoction methods, and administration routes all significantly impact efficacy. The place of origin determines the authenticity of medicinals, the growing environment affects their composition, harvesting time influences potency, improper storage leads to deterioration, quality control forms the foundation of efficacy, dosage forms and compatibility of medicinals affect absorption, dosing and decoction methods require precision, and administration routes should be tailored to individuals. Patient related factors include psychological state, individual differences, background, and disease condition. Psychological state affects treatment compliance, individual differences determine medicine responses, background influences patients' understanding of Chinese medicinals, and disease condition directly reflects efficacy. Practitioner related factors encompass theoretical knowledge, clinical experience, inherited practices, psychological state, and professional ethics. Theoretical knowledge guides medication use, clinical experience enhances efficacy, inherited practices influence prescribing styles, psychological state affects doctor–patient communication, and professional ethics ensure medical quality. These interrelated factors collectively influence the efficacy of Chinese medicinals, emphasizing the need for comprehensive consideration in clinical applications to achieve optimal therapeutic outcomes.